Hotspots Mapping for Preventing Bullying Through Design (Case Study: Public Junior High Schools in Malang City, Indonesia) - Makarim, Muhammad Raja Rafi; Titisari, Ema Yunita; Wulandari, Lisa Dwi (Civil and Environmental Science Journal (CIVENSE), 2025)
Bullying remains a critical issue in Indonesian schools, with spatial environments often influencing its occurrence. This study investigates the spatial distribution of bullying incidents across two public junior high schools in Malang City by using map-based surveys and spatial analysis. Data were collected through student questionnaires that identified bullying experiences and locations, followed by Kernel Density Estimation (KDE) using ArcGIS to identify bullying hotspots. The findings reveal that bullying is not randomly distributed but clusters in specific school areas such as classrooms, corridors, staircases, toilets, canteens, sports fields, and mosques. Physical bullying was more frequent in secluded, less supervised zones, while psychological bullying was concentrated in classrooms and semi-public social spaces. The study emphasizes the importance of spatial characteristics and supervision in shaping bullying patterns. It concludes that KDE is a valuable tool for informing design strategies and preventive interventions to create safer, more inclusive school-built environments.